Ceramic membrane for removing lithium ions from special glass strengthening agent and preparation method and removal method thereof
By using a ceramic membrane composed of specific oxides and boehmite nanosheets, combined with sol-gel method and ion exchange technology, the problems of complex operation and high cost of impurities removed by lithium ion in special glass are solved, and high efficiency is achieved Removal and stability improve glass performance and production efficiency.
Patent Information
- Application Number
- CN202411443732.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The prior art methods for removing lithium ions in special glass reinforcers have problems such as impurities introduction, complex operation, high cost and insufficient selectivity and stability of membrane materials, which affect glass performance and environmental pollution.
A ceramic film composed of silica, alumina, potassium oxide, sodium oxide, titanium oxide, zirconium oxide, cerium oxide and boehmite nanosheets was prepared and sintered by sol-gel method to form high selectivity and high adsorption Capacity membrane, combined with ion exchange technology to remove lithium ions, optimize component ratios and preparation process to improve removal efficiency and stability.
It achieves efficient removal of lithium ions, improves the mechanical strength and durability of glass, reduces environmental pollution, simplifies production processes, reduces costs, and maintains stable performance in high temperature and chemical corrosion environments.
Smart Images

Figure CN118955100B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of special glass production, and specifically relates to a ceramic membrane for removing lithium ions in a special glass strengthening agent, and a preparation method and a removal method thereof. Background Art
[0002] In the production process of special glass, chemical strengthening methods are often used to improve the strength and durability of glass. This is because chemical strengthening technology, also known as ion exchange technology, can form a compressive stress layer on the surface of glass, thereby significantly improving the mechanical strength of glass. This technology is widely used in the fields of construction, transportation, etc., especially in electronic products that require high damage resistance, such as touch screen covers of mobile phones and tablets.
[0003] During the chemical strengthening process, the glass is immersed in a molten salt containing alkali metal ions with a larger radius, so that the small-radius alkali metal ions on the glass surface are exchanged with the large-radius alkali metal ions in the molten salt. Due to the radius difference between the exchanged ions, the surface of the glass after ion exchange is in an extruded state, forming compressive stress, thereby improving the strength of the glass. The generation of this compressive stress can inhibit the further expansion of microcracks on the glass surface and improve the impact resistance and scratch resistance of the glass.
[0004] However, as the production process progresses, the lithium ion concentration in the solution increases, which can cause several problems. First, the increase in lithium ion concentration may reduce the ion exchange efficiency because the exchange rate of lithium ions with other ions in the molten salt (such as sodium ions or potassium ions) may slow down. Second, the accumulation of lithium ions may affect the stress distribution and uniformity of the glass, thereby affecting the performance of the final product. In addition, the accumulation of lithium ions may also lead to a shortened service life of the molten salt because the accumulation of lithium ions may change the chemical properties of the molten salt, thereby affecting its strengthening ability.
[0005] In order to solve these problems, some methods can be used to control and reduce the concentration of lithium ions in the solution. At present, the methods for removing lithium ions from special glass strengtheners mainly include chemical precipitation, ion exchange and membrane separation. These methods can remove lithium ions to a certain extent, but there are some obvious defects. For example:
[0006] 1. Chemical precipitation method: This method precipitates lithium ions by adding chemical reagents, but it is easy to introduce new impurities, affecting the purity and performance of the enhancer;
[0007] 2. Ion exchange method: Although this method can effectively remove lithium ions, it requires frequent replacement of ion exchange materials, which is complicated to operate and costly;
[0008] 3. Membrane separation method: This method uses the selective permeability of membrane materials to remove lithium ions, but the selectivity and stability of existing membrane materials still need to be improved.
[0009] Some patents have also been disclosed in the prior art. For example, CN117778749A discloses a method for recovering lithium from waste lithium-containing glass. An ion sieve is used to absorb lithium ions released from the waste lithium-containing glass into a molten salt bath. However, the ion sieve material is easily acid-lyzed and cannot operate stably under high temperature and strong acid-base environment. Summary of the invention
[0010] In view of the above-mentioned technical problems, the first object of the present invention is to provide a ceramic membrane for removing lithium ions in special glass strengtheners, which can effectively remove lithium ions in special glass strengtheners and improve ion exchange efficiency, thereby better improving the performance of special glass.
[0011] The second object of the present invention is to provide a method for removing the ceramic membrane of lithium ions in the special glass strengthening agent, which is simple to operate, improves the efficiency and product quality of special glass production, and reduces environmental pollution.
[0012] To achieve the above object, the technical solution adopted by the present invention is:
[0013] A ceramic membrane for removing lithium ions from a special glass strengthening agent, comprising the following components: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide, cerium oxide, and boehmite nanosheets.
[0014] The ceramic membrane of the present invention is composed of silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide, cerium oxide and boehmite nanosheets. These components work together to form a ceramic membrane with high selectivity and high adsorption capacity. Among them, silicon dioxide has high hardness and chemical stability, can form a strong network structure, ensure the mechanical strength and durability of the ceramic membrane, aluminum oxide has a high melting point and excellent mechanical properties, can improve the stability and strength of the ceramic membrane in a high temperature environment; silicon dioxide and aluminum oxide together provide the basic skeleton structure of the ceramic membrane, potassium oxide and sodium oxide can provide exchangeable potassium ions and sodium ions, exchange with lithium ions, thereby removing lithium ions in the solution, these alkali metal oxides can also reduce the melting point of the ceramic membrane and promote the sintering process, titanium dioxide has high hardness and corrosion resistance, can improve the wear resistance and chemical corrosion resistance of the ceramic membrane, zirconium oxide has high strength and high toughness, can remain stable at high temperatures, and prevent the ceramic membrane from deforming or breaking during use. Cracks, titanium dioxide and zirconium oxide enhance the mechanical strength and chemical stability of the membrane. Adding cerium oxide to the ceramic membrane can improve the catalytic activity of the membrane, promote the chemical reaction, and can be used as a sintering aid to adjust the porosity and pore size of the ceramic membrane by affecting the grain growth and densification during the sintering process. Boehmite nanosheets have a high specific surface area, which enables the ceramic membrane to provide more active sites to adsorb lithium ions, thereby improving the removal efficiency. In addition, boehmite nanosheets can also improve the pore structure of the ceramic membrane, giving it a more uniform pore size distribution, further improving the membrane's filtration performance and ion transfer efficiency. Boehmite nanosheets also have good chemical stability and can resist acid and alkali corrosion, which enables the ceramic membrane to maintain stable performance in different chemical environments.
[0015] As a further improvement of the above scheme, the weight percentages of the components are: 20.5-50% silicon dioxide, 20.5-25% aluminum oxide, 0-7% potassium oxide, 20-50% sodium oxide, 0-5% titanium dioxide, 0-10% boron oxide, 2-5% zirconium oxide, 2-10% cerium oxide, and 5-20% boehmite nanosheets. The optimization of these proportions enables the ceramic membrane to have higher efficiency and stability when removing lithium ions. Specifically, the ratio of silicon dioxide and aluminum oxide ensures the structural stability of the membrane, the ratio of potassium oxide and sodium oxide adjusts the ion exchange capacity of the membrane, the ratio of titanium dioxide and zirconium oxide enhances the mechanical strength and chemical stability of the membrane, the ratio of cerium oxide improves the catalytic activity of the membrane, and the ratio of boehmite nanosheets increases the specific surface area and adsorption capacity of the membrane.
[0016] As a further improvement of the above scheme, the weight percentages of the components are: 25% silicon dioxide, 23% aluminum oxide, 3% potassium oxide, 20% sodium oxide, 2% titanium dioxide, 5% boron oxide, 2% zirconium oxide, 10% cerium oxide, and 10% boehmite nanosheets.
[0017] As a further improvement of the above scheme, the preparation process of the boehmite nanosheets is: adding boehmite powder to deionized water, adding a dispersant, using an ultrasonic disperser for ultrasonic treatment for 30-40 minutes, transferring the dispersed boehmite suspension to a high-pressure reactor, performing hydrothermal treatment at 180-200° C. for 10-12 hours, cooling to room temperature after hydrothermal treatment, and then centrifuging to remove the supernatant, repeatedly washing the precipitate with deionized water until the pH value of the washing liquid is close to neutral, and drying the washed precipitate at 60-80° C. to obtain dry boehmite nanosheet powder.
[0018] As a further improvement of the above scheme, the dispersant is selected from one of polyvinyl alcohol, sodium polyacrylate, carboxymethyl cellulose, polyvinyl pyrrolidone and sodium dodecyl sulfate.
[0019] A method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent comprises the following steps:
[0020] (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide and cerium oxide are mixed in a preset ratio, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol, wherein the preset ratio is: silicon dioxide 20.5-50%, aluminum oxide 20.5-25%, potassium oxide 0-7%, sodium oxide 20-50%, titanium dioxide 0-5%, boron oxide 0-10%, zirconium oxide 2-5%, cerium oxide 2-10%, boehmite nanosheets 5-20%;
[0021] (2) Sol-gel process: adding the dried boehmite nanosheet powder to the sol prepared in step 1 according to a certain proportion, stirring evenly to form a uniform mixed sol, pouring the mixed sol into a mold, performing gelation treatment, and forming a preliminary gel;
[0022] (3) Drying and heat treatment: The gel is dried at room temperature for 24-48 hours, and then gradually heated to 1000-1300°C in a furnace for sintering for 5-10 seconds;
[0023] (4) Tablet pressing: The sintered ceramic membrane is pressed into a sheet to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished.
[0024] As a further improvement of the above scheme, the acid is nitric acid or sulfuric acid, the concentration of which is 15-30%, and the pH value is adjusted to 5.3-6.5.
[0025] A method for removing a ceramic membrane for removing lithium ions from a special glass strengthening agent comprises the following steps:
[0026] (1) Immerse the special glass in a molten solution containing sodium nitrate and potassium nitrate, and perform ion exchange in a high-temperature molten state above 400°C for 2-4 hours;
[0027] (2) Take out the special glass, immerse the prepared ceramic membrane into the solution, and keep the solution stirring at room temperature for 12-24 hours;
[0028] (3) Take samples regularly to monitor the lithium ion concentration in the solution and adjust the dosage and replacement frequency of the ceramic membrane as needed.
[0029] As a further improvement of the above scheme, the mass ratio of sodium nitrate to potassium nitrate in the step is 1-3:1.
[0030] As a further improvement of the above scheme, the monitoring method in the step includes atomic absorption spectroscopy, ion selective electrode method, and inductively coupled plasma spectroscopy.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention realizes the efficient removal of lithium ions in the special glass strengthener and improves the ion exchange efficiency through the specific ceramic membrane components and structural design. By removing lithium ions, the influence of the increase of lithium ion concentration on the stress distribution and uniformity of the glass can be prevented, thereby improving the mechanical strength and durability of the special glass. By adding specific components such as zirconium oxide and cerium oxide, the thermal stability and mechanical strength of the ceramic membrane are improved, so that it can maintain stable performance even in high temperature and chemical corrosion environments. The introduction of boehmite nanosheets improves the pore structure of the ceramic membrane, so that it has a more uniform pore size distribution, further improving the filtration performance and ion transmission efficiency of the membrane. The boehmite nanosheets have good chemical stability, so that the ceramic membrane can maintain stable performance in different chemical environments.
[0032] (2) The present invention adds boehmite nanosheets as a component of the ceramic membrane, mixes them with other materials during the preparation process, and forms an overall structure through a sol-gel method or sintering process. This structure is usually more uniform and stable. Compared with using boehmite nanosheets as a coating, it improves the overall performance of the ceramic membrane, such as increasing the porosity, improving the pore structure, increasing the specific surface area, etc., so that the ceramic membrane has high selectivity and high adsorption capacity. The boehmite coating mainly affects the surface properties of the membrane, such as improving the heat resistance of the surface and improving the wettability of the electrolyte, but does not significantly affect the overall structure and porosity of the membrane. In addition, the addition of boehmite nanosheets as a component can resist acid and alkali corrosion, so that the ceramic membrane can maintain stable performance in different chemical environments;
[0033] (3) The present invention reduces the consumption of raw materials and energy and lowers production costs by optimizing the preparation method of the ceramic membrane. The sol-gel process and sintering step help to form a ceramic membrane with good mechanical properties and high adsorption capacity. The removal method provided is simple to operate and easy to implement, thereby improving the efficiency of special glass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a physical picture of the ceramic membrane product. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the technical solution, the present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0036] The preparation process of the boehmite nanosheets described in the following embodiment is: 10g of boehmite powder is added to deionized water, 0.1g of dispersant is added, and ultrasonic treatment is performed using an ultrasonic disperser for 35 minutes. The dispersed boehmite suspension is transferred to a high-pressure reactor and hydrothermally treated at 200°C for 10 hours. After the hydrothermal treatment, it is cooled to room temperature and then centrifuged to remove the supernatant. The precipitate is repeatedly washed with deionized water until the pH value of the washing liquid is close to neutral. The washed precipitate is dried at 80°C to obtain a dry boehmite nanosheet powder; the dispersant is selected from polyvinyl alcohol. Example 1
[0037] A ceramic membrane for removing lithium ions from a special glass strengthening agent, comprising the following components: 25% silicon dioxide, 23% aluminum oxide, 3% potassium oxide, 20% sodium oxide, 2% titanium dioxide, 5% boron oxide, 2% zirconium oxide, 10% cerium oxide, and 10% boehmite nanosheets.
[0038] A method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent comprises the following steps:
[0039] (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide and cerium oxide are mixed in the above proportions, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol. The acid is nitric acid with a concentration of 18%, and the pH value is adjusted to 5.8;
[0040] (2) Sol-gel process: adding the dried boehmite nanosheet powder to the sol prepared in step 1 according to a certain proportion, stirring evenly to form a uniform mixed sol, pouring the mixed sol into a mold, performing gelation treatment, and forming a preliminary gel;
[0041] (3) Drying and heat treatment: The gel was dried at room temperature for 30 h, and then gradually heated to 1000 °C in a furnace for sintering for 10 s.
[0042] (4) Tablet pressing: The sintered ceramic membrane is pressed into a sheet to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished. Example 2
[0043] A ceramic membrane for removing lithium ions from a special glass strengthening agent, composed of the following components: 20.5% silicon dioxide, 25% aluminum oxide, 7% potassium oxide, 22.5% sodium oxide, 5% titanium dioxide, 10% boron oxide, 3% zirconium oxide, 2% cerium oxide, and 5% boehmite nanosheets.
[0044] A method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent comprises the following steps:
[0045] (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide and cerium oxide are mixed in the above proportions, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol, wherein the acid is sulfuric acid with a concentration of 15%, and the pH value is adjusted to 6.5;
[0046] (2) Sol-gel process: adding the dried boehmite nanosheet powder to the sol prepared in step 1 according to a certain proportion, stirring evenly to form a uniform mixed sol, pouring the mixed sol into a mold, performing gelation treatment, and forming a preliminary gel;
[0047] (3) Drying and heat treatment: The gel was dried at room temperature for 48 h and then gradually heated to 1300 °C in a furnace for sintering for 5 s.
[0048] (4) Tablet pressing: The sintered ceramic membrane is pressed into a sheet to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished. Example 3
[0049] A ceramic membrane for removing lithium ions from a special glass strengthening agent, comprising the following components: 40.5% silicon dioxide, 20.5% aluminum oxide, 20% sodium oxide, 3% titanium dioxide, 5% zirconium oxide, 3% cerium oxide, and 8% boehmite nanosheets.
[0050] A method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent comprises the following steps:
[0051] (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide and cerium oxide are mixed in the above proportions, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol, wherein the acid is nitric acid with a concentration of 30%, and the pH value is adjusted to 5.3;
[0052] (2) Sol-gel process: adding the dried boehmite nanosheet powder to the sol prepared in step 1 according to a certain proportion, stirring evenly to form a uniform mixed sol, pouring the mixed sol into a mold, performing gelation treatment, and forming a preliminary gel;
[0053] (3) Drying and heat treatment: The gel was dried at room temperature for 24 h and then gradually heated to 1200 °C in a furnace for sintering for 6 s.
[0054] (4) Tablet pressing: The sintered ceramic membrane is pressed into a sheet to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished. Example 4
[0055] A ceramic membrane for removing lithium ions from a special glass strengthening agent, composed of the following components: 20.5% silicon dioxide, 20.5% aluminum oxide, 2% potassium oxide, 30% sodium oxide, 1% boron oxide, 2% zirconium oxide, 4% cerium oxide, and 20% boehmite nanosheets.
[0056] A method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent comprises the following steps:
[0057] (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide and cerium oxide are mixed in the above proportions, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol, wherein the acid is sulfuric acid with a concentration of 20%, and the pH value is adjusted to 5.6;
[0058] (2) Sol-gel process: adding the dried boehmite nanosheet powder to the sol prepared in step 1 according to a certain proportion, stirring evenly to form a uniform mixed sol, pouring the mixed sol into a mold, performing gelation treatment, and forming a preliminary gel;
[0059] (3) Drying and heat treatment: The gel was dried at room temperature for 35 h and then gradually heated to 1260 °C in a furnace for sintering for 7 s.
[0060] (4) Tablet pressing: The sintered ceramic membrane is pressed into a sheet to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished.
[0061] Comparative Example 1:
[0062] The difference between this comparative example and Example 1 is that the composition formula is different, and the other conditions and steps are the same. This comparative example is composed of the following components: 35% silicon dioxide, 23% aluminum oxide, 3% potassium oxide, 20% sodium oxide, 2% titanium dioxide, 5% boron oxide, 2% zirconium oxide, and 10% boehmite nanosheets.
[0063] Comparative Example 2:
[0064] The difference between this comparative example and Example 1 is that the composition formula is different, and the other conditions and steps are the same. This comparative example is composed of the following components: 35% silicon dioxide, 23% aluminum oxide, 3% potassium oxide, 20% sodium oxide, 2% titanium dioxide, 5% boron oxide, 2% zirconium oxide, and 10% cerium oxide.
[0065] Comparative Example 3:
[0066] The difference between this comparative example and Example 1 is that in the preparation of the ceramic membrane, the boehmite nanosheet powder is not directly added to the sol, but is coated on the surface of the ceramic membrane as a coating. The specific steps are as follows:
[0067] (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, zirconium oxide and cerium oxide are mixed in the above proportions, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol. The acid is nitric acid with a concentration of 18%, and the pH value is adjusted to 5.8;
[0068] (2) Sol-gel process: pouring the sol prepared in step (1) into a mold and performing gelation treatment to form a preliminary gel;
[0069] (3) Drying and heat treatment: The gel was dried at room temperature for 30 h, and then gradually heated to 1000 °C in a furnace for sintering for 10 s.
[0070] (4) Tableting: The sintered ceramic membrane is subjected to a tabletting process to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished;
[0071] (5) Preparation of boehmite nanosheet coating: mixing boehmite nanosheet powder with deionized water and polyvinyl alcohol to form a uniform coating suspension;
[0072] (6) Coating with boehmite nanosheet coating: The boehmite nanosheet coating is uniformly coated on the surface of the ceramic membrane prepared in step 4 by spraying. After coating, the ceramic membrane is placed at room temperature to dry to obtain a ceramic membrane product.
[0073] The ceramic membranes obtained in Examples 1-4 and Comparative Examples 1-3 were used to remove lithium ions from special glass strengthening agents. The specific removal method was as follows:
[0074] (1) Immerse the special glass in a molten solution containing sodium nitrate and potassium nitrate, and perform ion exchange in a high temperature molten state above 400°C for 4 hours. The mass ratio of sodium nitrate to potassium nitrate is 2:1.
[0075] (2) Take out the special glass, immerse the prepared ceramic membrane into the solution, and keep the solution stirred at room temperature for 24 hours;
[0076] (3) Take samples regularly and monitor the lithium ion concentration in the solution using the ion selective electrode method, and adjust the amount and replacement frequency of the ceramic membrane as needed.
[0077] The above monitoring results are shown in the following table:
[0078]
[0079] The ceramic membranes prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to a series of performance tests, such as mechanical strength test, thermal stability test and chemical stability test. The flexural strength of the ceramic membrane was determined by a three-point bending test. The ceramic membrane sample was placed on a three-point bending tester and pressure was gradually applied until the sample broke. The maximum breaking force was recorded and the flexural strength was calculated. The thermal stability of the ceramic membrane was determined by thermogravimetric analysis (TGA). The ceramic membrane sample was placed in a thermogravimetric analyzer and the temperature was gradually raised to 1000°C. The mass change of the sample was recorded and the thermal stability was evaluated. The chemical stability of the ceramic membrane was determined by an acid-base immersion test. The ceramic membrane sample was immersed in a nitric acid solution with a concentration of 20 mol / L, and samples were taken regularly to determine the mass change of the sample and the chemical stability was evaluated. The test results are shown in the following table:
[0080]
[0081] It should be noted that, in this article, the terms: include, contain and any other variants are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Specific examples are used in this article to illustrate the principle and implementation of the technical solution of the present invention. The above examples are only used to help understand the method of the present invention and its core idea. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements, modifications or changes can be made, and the above technical features can also be combined in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the present invention to other occasions without improvement, should be regarded as the protection scope of the present invention.
Claims
1. A ceramic membrane for removing lithium ions from a special glass strengthening agent, characterized in that: The invention is composed of the following components: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, boron oxide, zirconium oxide, cerium oxide and boehmite nanosheets; the weight percentage of each component is: silicon dioxide 20.5-50%, aluminum oxide 20.5-25%, potassium oxide 0-7%, sodium oxide 20-50%, titanium dioxide 0-5%, boron oxide 0-10%, zirconium oxide 2-5%, cerium oxide 2-10% and boehmite nanosheets 5-20%.
2. A ceramic membrane for removing lithium ions from a special glass strengthening agent according to claim 1, characterized in that: The weight percentages of the components are: 25% silicon dioxide, 23% aluminum oxide, 3% potassium oxide, 20% sodium oxide, 2% titanium dioxide, 5% boron oxide, 2% zirconium oxide, 10% cerium oxide, and 10% boehmite nanosheets.
3. The ceramic membrane for removing lithium ions from a special glass strengthening agent according to claim 1, characterized in that: The preparation process of the boehmite nanosheets is as follows: adding boehmite powder to deionized water, adding a dispersant, using an ultrasonic disperser for ultrasonic treatment for 30-40 minutes, transferring the dispersed boehmite suspension to a high-pressure reactor, performing hydrothermal treatment at 180-200° C. for 10-12 hours, cooling to room temperature after the hydrothermal treatment, and then centrifuging to remove the supernatant, repeatedly washing the precipitate with deionized water until the pH value of the washing liquid is neutral, and drying the washed precipitate at 60-80° C. to obtain dry boehmite nanosheet powder.
4. The ceramic membrane for removing lithium ions from a special glass strengthening agent according to claim 3, characterized in that: The dispersant is selected from one of polyvinyl alcohol, sodium polyacrylate, carboxymethyl cellulose, polyvinyl pyrrolidone and sodium lauryl sulfate.
5. A method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of sol: silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, titanium dioxide, boron oxide, zirconium oxide and cerium oxide are mixed in a preset ratio, deionized water is added, stirred evenly, and then acid is added to adjust the pH value to acidic, and stirring is continued to form a uniform sol, wherein the preset ratio is: silicon dioxide 20.5-50%, aluminum oxide 20.5-25%, potassium oxide 0-7%, sodium oxide 20-50%, titanium dioxide 0-5%, boron oxide 0-10%, zirconium oxide 2-5%, cerium oxide 2-10%, boehmite nanosheets 5-20%; (2) Sol-gel process: adding the dried boehmite nanosheet powder to the sol prepared in step (1) in proportion, stirring evenly to form a uniform mixed sol, pouring the mixed sol into a mold, performing gelation treatment, and forming a preliminary gel; (3) Drying and heat treatment: The gel is dried at room temperature for 24-48 hours, and then gradually heated to 1000-1300°C in a furnace for sintering for 5-10 seconds; (4) Tablet pressing: The sintered ceramic membrane is pressed into a sheet to obtain the desired sheet shape, and finally the pressed ceramic membrane is ground and polished.
6. The method for preparing a ceramic membrane for removing lithium ions from a special glass strengthening agent according to claim 5, characterized in that: The acid is nitric acid or sulfuric acid, and its concentration is 15-30%, and the pH value is adjusted to 5.3-6.
5.
7. A method for removing a ceramic film from a special glass strengthening agent for removing lithium ions, characterized in that: The following steps are involved: The special glass is immersed in a molten solution containing sodium nitrate and potassium nitrate, and ion exchange is performed in a high temperature molten state above 400°C for 2-4 hours; Take out the special glass, immerse the ceramic membrane as described in any one of claims 1 to 5 into the solution, and keep the solution stirred at room temperature for 12 to 24 hours; Take samples regularly to monitor the lithium ion concentration in the solution, and adjust the dosage and replacement frequency of the ceramic membrane as needed.
8. The method for removing a ceramic film for removing lithium ions from a special glass strengthening agent according to claim 7, characterized in that: The mass ratio of the sodium nitrate to potassium nitrate is 1-3:
1.
9. The method for removing a ceramic film for removing lithium ions from a special glass strengthening agent according to claim 7, characterized in that: The monitoring methods include atomic absorption spectrometry, ion selective electrode method, and inductively coupled plasma spectrometry.
Citation Information
Patent Citations
Method for recovering lithium from waste lithium-containing glass
CN117778749A
High-stability flaky ion exchanger as well as preparation method and application thereof
CN117447093A
Method of manufacturing lithium ion conductive glass ceramic
US20150162642A1